UMPSA Convocation Expo carries theme ‘Sustainable for a Madani Generation’ - Nur Hartini, Mohd Hatta (UMPSA, 2025)
GAMBANG, 2 November 2025 – The 20th Convocation Expo of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), themed ‘Sustainable for a Madani Generation’, reflects the university’s commitment to environmental sustainability, community well-being, and sustainable economic development.